The Development of Memory Mobile Games for Alzheimer's and Dementia Patients - Tahir, Nur Azimah; Senan, Norhalina (Applied Information Technology And Computer Science, 2021)
Brain It On! – Memory Game is a memory games that can aid improve memory abilities while also providing an activity for the target user. This memory game is targeted elderly with age 60 and above. In this memory game, there are three mini game such as Flip Card game, Jigsaw Puzzle game and Quiz game. There are a few memory games available on the market, but they are all geared at children and teenagers. Other than that, most of existing games must be purchased in order to play the full version. The existing games also have high levels of difficulty, making it tough for the elderly to succeed and complete the game. This is due to the fact that the game is on a mobile phone, and the majority of the elderly do not know how to operate it. Therefore, Game Development Life Cycle (GDLC) is used as a methodology to develop this game. This methodology's phases are all appropriate for developing this game and ensuring its success. The result from user testing shows that the game is entertaining and the difficulty suitable for the elderly. However, there are a few things that might be improved to make the game better in the future